BIOM-18. CLINICOGENOMIC PREDICTORS FOR THE PATTERN OF FAILURE IN HIGH-GRADE GLIOMA. (14th November 2022) - Kang, Byung-Hee; Ho Lee, Joo; Kim, Tae Min; Yun, Hongseok; Won, Jae-Kyung; Choi, Seung Hong; Lee, Soon-Tae; Park, Sung-Hye; Park, Chul-Kee
Abstract: Background: High-grade gliomas, the most common primary brain tumors, are highly lethal and treatment options remain limited. Despite advances in genomic technologies, there are few molecular biomarkers to guide precision medicine for high-grade glioma. Here, we aimed to identify the clinicogenomic features associated with its prognosis and recurrence patterns. MATERIALS/METHODS: Our single-institution retrospective analysis included 182 patients diagnosed with high-grade gliomas who underwent next-generation sequencing targeting 82 brain tumor-relevant genes. Clinicopathological status, treatment characteristics, survival, and genomic profiles were analyzed. RESULTS: At a median follow-up of 23 months (range, 2-229 months), 151 patients (83%) had progression or recurrences. Local and distant recurrences were observed in 132 (72.5%) and 101 (54.9%) patients, respectively. The most common genomic variants in high-grade gliomas were TP53 (42.9%), IDH1/2 (23.1%), TERT promoter (38.5%), ATRX (13.2%), H3F3A (7.1%), and SETD2 (6.0%) mutation. Regarding copy number variants, amplification of EGFR (20.9%), PDGFRA (9.9%), MYCN (2.2%) and loss of CDKN2A/2B (49.5%), PTEN (37.9%), RB1 (17.6%), and 1p19q codeletion(9.3%) were the most common copy number aberrations. On multivariate cox regression anlalysis, MYCN amplification (HR 6.08 95% CI 1.91-19.35, p = 0.002), and SETD2 mutation (HR 0.19 95% CI 0.06-0.62, p =0.06) were independent predictors of overall survival, in relation to previously established prognostic factors including age, Eastern Cooperative Oncology Group Performance Status (ECOG PS) scale, extent of resection, MGMT promoter methylation, and IDH1/2 mutation. Interestingly, MYCN amplification (HR 5.24 95% CI 1.69-16.27, p = 0.004), SETD2 mutation (HR 0.35 95% CI 0.12-0.99, p =0.048) were independent predictors of failure from distant recurrences. CONCLUSION: The assessment of genomic characteristics in conjunction with pattern of failure for high-grade glioma aids to identify patients who are likely to benefit from personalized medicine. We identified SETD2 mutation, and MYCN as a prognostic biomarkers with potential therapeutic implications in patients with high-grade glioma.